(untitled) (Comprehensive Journal of Science, 2025)
This study examines the relationship between road geometric design and traffic safety on one hand, and the environmental impacts resulting from accidents on the other. The research is based on both field and statistical analyses of accident data in the Municipality of Zliten during the period from 2020 to 2025. The study relied on official data collected from relevant authorities’ reports, including indicators such as the number of accidents, fatalities, injuries, and financial losses, in addition to the spatial and temporal distribution of these accidents according to road type (coastal, rural, internal, and main). The results revealed a significant increase in accident and fatality rates on rural and coastal roads due to deficiencies in design standards, such as the absence of barriers, poor lighting, and inadequate drainage systems. Furthermore, the analyses indicated both direct and indirect environmental effects, including animal deaths, agricultural land pollution caused by oil and fuel leakage, and the reduction of cultivated areas as a result of unplanned infrastructure expansion. The study concluded that it is essential to reconsider road engineering specifications, particularly in rural and agricultural areas, and to link road projects with sustainable environmental planning. It also presented a set of practical and legislative recommendations to support the improvement of environmental and traffic safety in Zliten, thereby reducing human, economic, and environmental losses.